IBU SEBAGAI MADRASAH DALAM PENDIDIKAN ANAK - Fithriani Gade (Jurnal Ilmiah Didaktika, 2012)
Mother is an important â€œschoolâ€ in constructing childrenâ€™s integrity. Besides, she acts as a central figure that must be imitated through directions of good deeds. To achieve the values, as to inculcate good behavior in family and society, hence, mothers need to concern on their children from the early childhood on every negative attitude arise such as arrogant and proud which must be cured immediately. If the characters being maintained, then, in times to come their attitudes tend to not listen to the good advices and they do not want to engage in another good group. In this case, the influence is not only from societal environment but also family. Moreover, if they live in the broken familywhere in which inharmonic sphere and does not colored by Islamic values, then, their psychological aspects will be destructed and far away from Islamic values. To solve this problem, mother is as an important figure to make her family peace for their children succeed in the future lives.